Personality traits of successful music entrepreneurs - Paul Loeb van Zuilenburg (Acta Academica, 2013)
It is internationally accepted that music entrepreneurship presents an alternative form of employment for music graduates. The question that inadvertently arises concerns the suitability of this occupation for musicians. During this study, musicians and successful music entrepreneurs were interviewed in order to identify their critical personality traits. These were compared with the documented personality traits of entrepreneurs and the findings showed a strong correlation between the character traits of both groupings, but with critical differences apparent. The article presents a typology of personality traits and concludes that not all musicians are suited to a career in music entrepreneurship.